Expression of functional neurotransmitter receptors in Xenopus oocytes after injection of human brain membranes - Miledi, Ricardo (The National Academy of Sciences, 2002)
The Xenopus oocyte is a very powerful tool for studies of the structure and function of membrane proteins, e.g., messenger RNA extracted from the brain and injected into oocytes leads to the synthesis and membrane incorporation of many types of functional receptors and ion channels, and membrane vesicles from Torpedo electroplaques injected into oocytes fuse with the oocyte membrane and cause the appearance of functional Torpedo acetylcholine receptors and Cl(−) channels. This approach was developed further to transplant already assembled neurotransmitter receptors from human brain cells to the plasma membrane of Xenopus oocytes. Membranes isolated from the temporal neocortex of a patient, operated for intractable epilepsy, were injected into oocytes and, within a few hours, the oocyte membrane acquired functional neurotransmitter receptors to γ-aminobutyric acid, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid, kainate, and glycine. These receptors were also expressed in the plasma membrane of oocytes injected with mRNA extracted from the temporal neocortex of the same patient. All of this makes the Xenopus oocyte a more useful model than it already is for studies of the structure and function of many human membrane proteins and opens the way to novel pathophysiological investigations of some human brain disorders.